Analysis Of Cash Ratio (CR), Debt To Equity Ratio (DER), And Return On Equity (ROE) On Ecomonic Value Added (EVA) In Digital Banks - Sevina Hanisa Anindya; Yoyo Sudaryo; Dayan Hakim Natigor Sipahutar; Nunung Ayu Sofiati; Gurawan Dayona Ismail (Green Publisher Indonesia, 2024)
This study evaluates the performance of digital banks in Indonesia during 2020-2023 as a real form of digitalization, focusing on the effect of Cash Ratio, Debt to Equity Ratio, and Return on Equity on Economic Value Added (EVA) in digital banks. The research method used is quantitative method with descriptive and verification approaches. The data source used is secondary data with purposive sampling and the companies selected from the criteria are 7 digital bank companies for 4 periods, so that the sample used in this study is 28 samples. The data used in this study are secondary data in the form of annual reports going public on the bank company website. The analysis technique used in this research is regression with panel data using the Eviews program. The results of this study indicate that the significance value of the cash ratio t test T count -0.910149 < T table 2.05553, and a sig value of 0.3718> 0.05 means that the Cash Ratio has no effect on Economic Value Added in 7 digital bank companies. The significance value of the Debt to Equity Ratio T test shows the value of T count -2.272184> T table 2.05553, and the sig value of 0.0323 <0.05. The significance value of the Return on Equity T test shows the value of T count -0.608342 < T table 2.05553, and the sig value of 0.35487> from 0.05 means that Return on Equity has no effect on Economic Value Added in 7 digital bank companies in Indonesia.